Small-signal modeling, stability analysis, and controller design of grid-friendly power converters with virtual inertia and grid-forming capability - Deng, Han (2019)
Distributed virtual inertia provided by grid-friendly power converters is emerging as an effective way for inertia enhancement and frequency regulation improvement in more-electronics power systems. However, most existing methods attempt to generate distributed virtual inertia by grid-following power converters. As compared with conventional grid-feeding power converters, grid-forming power converters, i.e. the ones controlled as ac voltage sources, are more promising owing to their capabilities of voltage and frequency regulation. As such, this paper explores the possibility of inertia emulation by grid-forming power converters. Through the stability analysis, it is revealed that the instability issue is associated with typical virtual inertia control. Further, a lead-lag compensator is introduced to resolve this issue. To better stabilize the system, a detailed small signal model is derived, and the sensitivity analysis is applied to study the critical poles.